Manifestasi Kehadiran Tuhan di dalam Teologi Kristen: Dari Tabernakel Musa ke Bait Allah yang Hidup - Sonny Zaluchu (UIN Sunan Gunung Djati, 2021)
This paper aims to prove that the manifestation of God's presence in the Old Testament (OT) is not something final. The climax of God's presence among His people is seen in the coming of Jesus into the world through the incarnation. Through this paper, it is explained that even though God is transcendent in Christian theology, He is also immanent at the same time. God's transcendence cannot be separated from his immanent nature and vice versa. The main data used in this research is through a literature review. The results obtained from the literature review were compiled through the Integrative Critical Analysis (ICA) approach to meet the research objectives. The main conclusion is, theologically, the Christian is the abode of the true God.